E-Procurement Service Quality in Malaysia - Latifah binti Syed A Kadir, Shafirah (ASEAN Marketing Journal, 2021)
The government in Malaysia has fully adopted and developed the applications and practices of information communication technologies (ICTs) to provide better online services to enhance the government’s credibility. To understand service quality issues within this new delivery channel, this paper investigates e-procurement portal/websites through the use of E-Service-Quality (E-S-QUAL) and E-Recovery Service-Quality (E-RecS-QUAL) scales by employing a questionnaire survey distributed to 400 respondents. The collected data were analyzed using Smart PLS 3.0 to test the relationships among efficiency, system availability and privacy, responsiveness, and contact. The results show that both E-S-QUAL and E-RecS-QUAL strongly influence perceived service quality and behavioral intentions. In addition, the evidence of perceived service quality in its role as a mediator was significant. The findings constitute an empirical contribution to the literature on the application of electronic service quality.